2018
DOI: 10.1002/er.4055
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of active modular internal combustion engine concept: Targeting efficiency increase and carbon dioxide emissions reduction of gasoline engines

Abstract: Summary Today's gasoline engines use a group of new technologies to fulfill emission legislation and at the same time improve fuel consumption with excellent drivability performance and increase specific power and torque output. One technology group focuses on the improvement of efficiency at low loads which includes variable charge motion, variable valve actuation, GDI stratified, and homogenous injection, and the other group shifts the engine operating point towards more efficient operating areas by using su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The main role of this pollution is the emission of exhaust gases from motor vehicles [3,4]. Replacing or modifying of fossil fuels with renewable clean fuel is a very sensible way to prevent fuel shortages for the automotive industry [5,6]. Alcohol has been used as alternative fuel for engines since the 19th century [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The main role of this pollution is the emission of exhaust gases from motor vehicles [3,4]. Replacing or modifying of fossil fuels with renewable clean fuel is a very sensible way to prevent fuel shortages for the automotive industry [5,6]. Alcohol has been used as alternative fuel for engines since the 19th century [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The energy loss in thermal power equipments could not be evaluated based on only the first law of thermodynamics [12]. The experimental investigation on the CI engine both by quantitative and qualitative methods based on thermodynamic I and II law respectively indicated that the exergy is a important measure of engine performance [13]. The energetic and exergetic efficiency were found to be higher in simarouba bio diesel blends than in diesel [14].…”
Section: Introductionmentioning
confidence: 99%
“…To control this pollution, governments have introduced several regulations to reduce the vehicular emissions [3]. These regulations stimulate automotive industries to develop vehicles with high efficiency, low fuel consumption, and low emissions [4].…”
Section: Introductionmentioning
confidence: 99%